Explore the Diagnostic Efficiency of Chinese Thyroid Imaging Reporting and Data Systems by Comparing With the Other Four Systems (ACR TI-RADS, Kwak-TIRADS, KSThR-TIRADS, and EU-TIRADS): A Single-Center Study - Qi, Qi; Zhou, Aiyun; Guo, Suping; Huang, Xingzhi; Chen, Songli; Li, Yaohui; Xu, Pan (Frontiers in Endocrinology, 2021)
Purpose:To explore the characteristics of C-TIRADS by comparing it with ACR-TIRADS, Kwak-TIRADS, KSThR-TIRADS and EU-TIRADS. Methods:A total of 1096 nodules were collected from 884 patients undergoing thyroidectomy in our center between May 2018 and December 2020. Divided the nodules into two groups: “＞10mm” and “≤10mm”.The maximum diameter and ultrasound characteristics of each nodule were observed and recorded, then classified based on ACR-TIRADS, Kwak-TIRADS, KSThR-TIRADS，EU-TIRADS, and C-TIRADS. Results:A total of 682 benign nodules cases (62.23%) and 414 malignant nodules cases (37.77%) were identified. The nodule malignancy rates in the groups(Kwak-TIRADS 4B，C-TIRADS 4B、4C) of two sizes were significantly different (all p<0.05). There was no statistical difference in the other grades of two sizes (all p＞0.05). Unnecessary biopsy rates were the lowest in C-TIRADS(49.02% p＜0.001).Furthermore, Kwak-TIRADS had the highest sensitivity and NPV (89.9%，91.0%,all p＜0.05), while C-TIRADS had the highest specificity and PPV (82.3%,69.2%,all p＜0.05). C-TIRADS and Kwak-TIRADS had the highest accuracy(76.0%,72.5%,P=0.071).The AUCs of the 5 guidelines were C-TIRADS(0.816, P＜0.05),Kwak-TIRADS(0.789, P＜0.05) KTA/KSThR-TIRADS and ACR-TIRADS(0.773,0.763,P=0.305), EU-TIRADS(0.734, P＜0.05) .The AUCs of the five guidelines were not statistically different between“nodules＞10mm” and“ nodules≤10mm ”(all P>0.05). Conclusions: C-TIRADS could minimize the panicking in patients by reducing the classification of nodules without affecting the puncture standards. C-TIRADS was slightly efficient than Kwak-TIRADS,KTA/KSThR-TIRADS and ACR-TIRADS , and had greater advantages than EU-TIRADS.The diagnostic abilities of the five guidelines for “nodules≤10mm ” were not inferior to that of “nodules＞10mm”.C-TIRADS is simple and easy to implement and can provide effective thyroid tumor risk stratification for thyroid nodule diagnosis, especially in China.